1984
DOI: 10.1128/aac.26.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Duodeno-pancreatic secretions enhance bactericidal activity of antimicrobial drugs

Abstract: We have studied the action of various antimicrobial agents in microbiological media and in human duodenopancreatic secretions. In the latter medium, clioquinol exhibited a rapid bactericidal effect on both growing and stationary bacteria at concentrations near its MIC. However, it was merely bacteriostatic in microbiological media, even at high concentrations. Phanquinone, chlorquinaldol, and, to a lesser extent, also chloramphenicol and trimethoprim likewise displayed enhanced bactericidal activity in duodeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 5 publications
0
7
1
Order By: Relevance
“…This pH effect was demonstrable in canine prostatic secretion and human urine ( Table 3) and suggests that it might be worthwhile to adjust pH to around 7.0 when treating urinary tract infections with fleroxacin. Interaction between body fluids and antimicrobial agents has been previously described (16,21). In our study, however, the investigated body fluids had no significant effect on MIC, indicating that the antibacterial activity of fleroxacin would be unaffected by prostatic secretion and urine.…”
Section: Discussioncontrasting
confidence: 50%
“…This pH effect was demonstrable in canine prostatic secretion and human urine ( Table 3) and suggests that it might be worthwhile to adjust pH to around 7.0 when treating urinary tract infections with fleroxacin. Interaction between body fluids and antimicrobial agents has been previously described (16,21). In our study, however, the investigated body fluids had no significant effect on MIC, indicating that the antibacterial activity of fleroxacin would be unaffected by prostatic secretion and urine.…”
Section: Discussioncontrasting
confidence: 50%
“…1B) is an interesting 8-hydroxyquinoline-based hit that might serve as a potential starting point for medicinal chemistry. Other hits that may be of interest as tool compounds, though not chemically attractive for drug discovery, include SAHH-2, a quinazosin, a known vasodilator with alpha-1 adrenergic receptor as its target [40] and SAHH-3, known as phanquinone, an antimicrobial agent [41]. …”
Section: Resultsmentioning
confidence: 99%
“…Anomalous enhancement activity of serum has been reported (13,18,19,28,33). Serum enhancement of antibiotic activity can be attributed to various factors, including the influence of serum on growth of the bacteria (2), serum alpha-2-globulin (22), changes in the pH of the test media (8), antibacterial peptides (4), or as yet unidentified synergistic host factors (18,19,21). Leggett and Craig (19) have shown that the increases in the MICs of ceftriaxone and other highly protein bound cephalosporins observed in the presence of albumin were significantly less than those predicted when they were determined in serum-containing medium and were not predicted from the protein-binding properties of the antibiotics.…”
Section: Discussionmentioning
confidence: 99%